Investigation of Surplus (Deficit) Underwriting of Tabarru' Fund on BNI Life Insurance Unit Syariah - Baso Akib; Muh. Takbir Gawy Al Buny MYS; Jawad Z. Salic (Journal of Management Economic and Financial, 2024)
This study examines the factors influencing the underwriting surplus (deficit) of tabarru' funds in BNI Life Insurance's sharia unit between June and July 2023. Utilizing a quantitative and descriptive methodology, the research relies on secondary data sourced from BNI Life Insurance's sharia unit financial reports spanning from 2015 to 2022. The sampling technique employed is a saturated sample, encompassing 32 time-series data points extracted from quarterly financial reports. Data collection methods include observation and documentation, with analysis conducted using multiple linear regression analysis through IBM SPSS version 20. The findings indicate that participant contributions have a positive and significant influence on the underwriting surplus (deficit) of tabarru' funds, whereas investment income and claims have a negative and significant impact. Collectively, participant contributions, investment income, and claims significantly affect the underwriting surplus (deficit). The results suggest that enhancing management practices and ensuring the stability of participant contributions, investment income, and claims could improve the underwriting surplus of BNI Life Insurance's sharia unit. The research implies that better company management, coupled with the provision of sharia-compliant products, can increase customer loyalty and public interest, thereby boosting the company's assets.